OPTIMALISASI PENGEMBANGAN KOGNITIF ANAK TK A MENGGUNAKAN ALAT PERMAINAN EDUKATIF MATCH COLOUR FINE MOTOR BALL DI TK BUMITAMA - Eka Astuti, Retno; Intan Rochmawati, Nur; Himmah Taulany, Himmah; Swantyka Ilham Prahesti, Swantyka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT Cognitive learning in early childhood requires concrete media appropriate to the pre-operational developmental stage. However, learning practices at Bumitama Kindergarten are still dominated by verbal methods and worksheets, resulting in children being less active, easily bored, and experiencing difficulty recognizing and matching colors. This study aims to describe cognitive learning practices before the use of the media, analyze the effectiveness of the Match Color Fine Motor Ball Educational Game Tool (APE), and identify improvements in children's cognitive abilities and hand-eye coordination. This study used a best practice approach with 15 grade A children of Bumitama Kindergarten as subjects. Data collection techniques were conducted through observations before and after the media implementation using the developmental indicators of BB, MB, BSH, and BSB. The results showed a decrease in the Not Developing (BB) category from 7 children to 2 children and an increase in the Very Well Developing (BSB) category from 1 child to 6 children. These findings indicate that the use of the Match Color Fine Motor Ball Educational Game Tool (APE) is effective in improving children's color recognition, color matching, and fine motor coordination. Play-based media and concrete object manipulation have been proven to create more active, enjoyable, and meaningful learning for early childhood.